HUBUNGAN ANTARA KOMUNIKASI POSITIF DALAM KELUARGA DENGAN ASERTIVITAS PADA SISWA SMP NEGERI 2 DEPOK YOGYAKARTA - Miasari, Astri (EMPATHY Jurnal Fakultas Psikologi, 2012)
ABSTRACT This study aimed to determine the relationship between positive communication in families with assertiveness in students of SMP Negeri 2 Depok. Subjects in this study were students of class VII SMP Negeri 2 Depok are living with a family member who is a nuclear family in which both parents and siblings. Methods of data collection in this study using a scale of positive communication within the family and assertiveness scale. The sampling technique used in this study is cluster random sampling. Analysis using the product moment correlation. Computing data using SPSS 16.0 for windows. Based on the above analysis, the hypothesis proposed in this study is the positive relationship between positive communication in families with assertiveness can be received with a correlation coefficient of 0.669 with a significance level of 0.000 (p <0.01). Effective contribution of positive communication in families with assertiveness by 44.7% and 55.3% were contributed by other factors. The results of this study stated that there was a significant positive relationship between positive communication in families with assertiveness SMP Negeri 2 Depok. The higher the communication that exists within the family, the higher the student assertiveness, conversely the lower the positive communication that exists in the family will get low assertiveness owned by students. Keywords: assertiveness, positive communication in the family